2020
DOI: 10.4018/978-1-5225-8933-4.ch023
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Google Analytics for Measuring Website Performance of Non-Formal Education Institution

Abstract: The purpose of this chapter is to measure the performance of a non-formal educational institution's website using Google Analytics data and data obtained in a separate research on specific non-formal educational institution's users. The goal was to determine the best performing acquisition channel for non-formal educational institutions and the average user profile of this kind of educational programs by means of user acquisition and behavior data. Key parameters used to measure the performance of different ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…The idea is to provide recommendations for training initiatives that will help persons with disabilities in Serbia to get involved in the online labor market. This is in accordance with the fact that non-formal educational programs are experiencing growing popularity worldwide (Domazet & Simović, 2019). Furthermore, it is our opinion that persons with disabilities are not fully aware of the potential of digital labor platforms and digital entrepreneurship for self-employment.…”
Section: Discussionsupporting
confidence: 77%
“…The idea is to provide recommendations for training initiatives that will help persons with disabilities in Serbia to get involved in the online labor market. This is in accordance with the fact that non-formal educational programs are experiencing growing popularity worldwide (Domazet & Simović, 2019). Furthermore, it is our opinion that persons with disabilities are not fully aware of the potential of digital labor platforms and digital entrepreneurship for self-employment.…”
Section: Discussionsupporting
confidence: 77%
“…Google Analytics can be used to determine the growth of website traffic [16], Based on the results of Google Analytics for the last 90 days, it can be concluded that the implementation of SEO on the Dusun Nusantara web-based application has succeeded in increasing the number of users and sessions on the application. During this period, the number of users reached 2,300 people and the number of sessions reached 2,900, indicating an increase in user interest in visiting the application.…”
Section: Methodsmentioning
confidence: 99%
“…Analytics can help the developer to track users and improve customer satisfaction. The most common method to collect web traffic for a website is Google Analytics [18]. c Bounce rate Like most of the metrics used in Google Analytics, the bounce rate is also a measure of visitors' lack of interest in a specific website when they arrive there from search engines.…”
Section: Small Business B2b Websites Figure 3 Small Business B2b Webs...mentioning
confidence: 99%